2016
DOI: 10.17221/8770-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of serum amyloid A, haptoglobin, tumour necrosis factor and interleukin-1 and -6 in Anatolian buffaloes naturally infected with dermatophytosis-

Abstract: ABSTRACT:Dermatophytosis is most frequently found in ruminants, in which non-pruritic periocular lesions are most typical, though generalised skin disease may develop. Accordingly, the infection causes major economic losses. The aim of this study was to measure the inflammatory status of Anatolian buffaloes with dermatophytosis by determining the serum concentrations of serum amyloid A (SAA), haptoglobin (Hp), tumour necrosis factor (TNF-α) and interleukin-1 (IL-1) and -6 (IL-6). Anatolian buffaloes (n = 26), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
(7 reference statements)
2
11
2
Order By: Relevance
“…In this study, the RI for haptoglobin in serum of healthy buffalo calves ranged between 0.02 and 0.56 g/L, with average of 0.17 g/L (Table 3). These results are higher than measured in 3-11-month-old healthy buffaloes (average of 0.008 g/L) (Kabu and Sayin 2016) and adult buffaloes (average of 0.11 g/L) (El-Ashker et al 2013) but lower than the observed in newborn bovine calves, with average of 0.23 g/L (Nikunen et al 2007) and 0.27 g/L (Tóthová et al 2015). Also, studies in healthy adult cattle showed that haptoglobin blood serum concentrationcan range between 0.02 and 0.10 g/L ) and that concentrations below 0.35 g/L indicates that animals are healthy, different from the buffalo calves from this study (Table 3), where upper limit for haptoglobin were higher (0.56 g/L).…”
Section: Resultscontrasting
confidence: 72%
See 1 more Smart Citation
“…In this study, the RI for haptoglobin in serum of healthy buffalo calves ranged between 0.02 and 0.56 g/L, with average of 0.17 g/L (Table 3). These results are higher than measured in 3-11-month-old healthy buffaloes (average of 0.008 g/L) (Kabu and Sayin 2016) and adult buffaloes (average of 0.11 g/L) (El-Ashker et al 2013) but lower than the observed in newborn bovine calves, with average of 0.23 g/L (Nikunen et al 2007) and 0.27 g/L (Tóthová et al 2015). Also, studies in healthy adult cattle showed that haptoglobin blood serum concentrationcan range between 0.02 and 0.10 g/L ) and that concentrations below 0.35 g/L indicates that animals are healthy, different from the buffalo calves from this study (Table 3), where upper limit for haptoglobin were higher (0.56 g/L).…”
Section: Resultscontrasting
confidence: 72%
“…In buffaloes, studies with alterations in the hemogram and APP in newborn diseased animals are scarce (Clemente et al 2016;Kabu and Sayin 2016). In adult buffaloes, studies have shown important alterations in blood serum components in animals with traumatic reticuloperitonitis and pericarditis (Saleh et al 2008;El-Ashker et al 2013;Neamat-Allah 2015), abomasal ulcer (Tajik et al 2012), animals experimentally infected with Pasteurella multocida (Horadagoda et al 2001(Horadagoda et al , 2002, with uterine torsion (Ali et al 2011), and in animals with fever, parasitic infestations, and respiratory disorders (Singh et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Localized infections also elicit immune responses that can be measured in circulation. Anatolian buffaloes with infectious skin lesions exhibit elevated TNF-α and IL-6 compared to healthy controls [ 70 ], and here tusk infections were associated with increased pro- and anti-inflammatory cytokines TNF-α and IL-10, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Trichophytosis is a group of outside infection of keratinized tissues such as leather, bristle, feather and hoofs in humans and animals (Aslan et al 2010, Kabu andSayın 2016). Kabu and Sayın (2016) reported that Anatolian buffaloes was trichophytosis.…”
Section: Introductionmentioning
confidence: 99%